2019
DOI: 10.24911/sjp.106-1535804613
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima media thickness in children with nephrotic syndrome: an observational case control study

Abstract: Carotid intima media thickness (cIMT) is considered as a surrogate marker for the various cardiovascular events that complicate nephrotic syndrome (NS). The present work was conducted to study cIMT in children with NS and to find out its correlation with dyslipidemia and other risk factors. This was a case control study conducted at a tertiary care hospital in children with NS who were more than 2 years with normal serum complement, being on therapy for NS for at least 1 year, glomerular filtration rate more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…We had not found any correlation of CIMT with blood pressure, and this could be because only 12.2% of our NS children were hypertensive. Similar to our results, Mehta et al 21 reported no significant correlation between CIMT and blood pressure. Moreover, there were no significant correlations between CIMT and lipid profile in our patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We had not found any correlation of CIMT with blood pressure, and this could be because only 12.2% of our NS children were hypertensive. Similar to our results, Mehta et al 21 reported no significant correlation between CIMT and blood pressure. Moreover, there were no significant correlations between CIMT and lipid profile in our patients.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were documented in the study by Hooman et al 20 who declared that common carotid artery CIMT in the patients group (0.42 ±.14) was higher than that of the control group (0.37 ±.08, p<0.05). Correspondingly, Mehta et al 21 in their study conducted on 66 children with NS and 128 age and sex matched healthy controls, found that CIMT was significantly higher in NS especially in the age above 4 years. However, unlike our results, Kniazewska et al 9 found no significant differences in CIMT between 30 children previously treated for nephrotic syndrome versus 30 healthy children.…”
Section: Discussionmentioning
confidence: 87%
“…Ordonez et al, 1993 [9] The Thickness of carotid intima-media thickness (cIMT) was higher in NS children as compared to control group in all the ages, but this difference was statistically significant only after 4 years of age [5]. There was statistically significant positive correlation between cIMT and age, duration of disease and number of relapses.…”
Section: Correlation With Other Parametersmentioning
confidence: 96%
“…In general, dyslipidemia accelerates atherosclerosis, and increases risk of myocardial infarction (MI) and cerebrovascular accident. Collected literatures on NS and the makers for atherosclerosis and cardiovascular events were shown in Table 1 [5,6,[9][10][11][12][13][14].…”
Section: Ns and Atherosclerosis And Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
See 1 more Smart Citation